2021
DOI: 10.4103/ijo.ijo_3632_20
|View full text |Cite
|
Sign up to set email alerts
|

Red reflex test screening for neonates: A systematic review and meta analysis

Abstract: Red reflex test (RRT) screening is yet to be a part of the neonate's normal examination before discharge from hospital in a majority of low- and middle-income countries. The purpose was this review was to systematically evaluate the diagnostic accuracy of RRT for the detection of ocular abnormalities in newborns. PubMed, EMBASE, Scopus, Web of Science, and Cochrane database of systematic reviews were the data sources. Quality of Diagnostic Accuracy Studies-2 (QUADAS-2) was utilized for quality assessment of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…Our review suggests that red reflex testing is reasonably sensitive (67%, 95% CI = 9%-99%) for clinically significant anterior segment conditions, which is acceptable for screening purposes in most settings. However, we identified only one high-quality study [24] We identified two other DTA reviews of red reflex testing in newborns, which report lower sensitivities (23% and 17.5%) [34,35]. The high specificities reported (98% and 97.5%) are comparable to the study we report.…”
Section: Discussionsupporting
confidence: 58%
“…Our review suggests that red reflex testing is reasonably sensitive (67%, 95% CI = 9%-99%) for clinically significant anterior segment conditions, which is acceptable for screening purposes in most settings. However, we identified only one high-quality study [24] We identified two other DTA reviews of red reflex testing in newborns, which report lower sensitivities (23% and 17.5%) [34,35]. The high specificities reported (98% and 97.5%) are comparable to the study we report.…”
Section: Discussionsupporting
confidence: 58%
“…[ 6 ] In a large meta-analysis published in this issue of Indian Journal of Ophthalmology, the authors seem to confirm the low sensitivity (23%) and high specificity (98%) of the red reflex test but show that the test is excellent for the detection of anterior segment anomalies (99.2%) as compared to disorders of the posterior segment (14.1%). [ 7 ]…”
Section: Is Red Reflex Test Reliable?mentioning
confidence: 99%
“…The patients' general health and satisfaction were assessed using the Short Form Health Survey-36 and the Global Rating of Change score, respectively. Before therapy, 3, 6, and 24 weeks after treatment, the variations (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) in dependent factors were investigated. In every parameter that measures success.…”
mentioning
confidence: 99%